Heat transfer characteristics of high crossflow impingement channels: Effect of number of holes. (August 2015) - Llucià, S; Terzis, A; Ott, P; Cochet, M
In modern turbine airfoils, narrow impingement cooling channels can be formed in a double-wall configuration. In these wall-integrated cooling cavities, the generated crossflow is one of the most important design factors, and hence, the number of impingement holes included in a channel. This study examines experimentally the influence of the number of impingement holes on the heat transfer characteristics of narrow impingement channels. The channels consist of two rows of jets where the number of holes in the axial direction is varied from 5 to 10, maintaining the same jet plate open area. Local heat transfer coefficient distributions are obtained for all channel interior walls using the transient liquid crystal technique and over a range of Reynolds numbers (20, 300–41, 500). The results show an important heat transfer degradation at higher open areas and a small influence of the number of holes at upstream channel positions.